Examining the planning model and rationality values of Singapore’s state planning: Is it effective and successful? - Muhamad Khoirul Anam; Muhammad Rifqi Al Faizi (Priviet Social Sciences Journal, 2026)
National planning plays a crucial role in navigating the increasing complexity of modern development, which is marked by rapid urbanization, climate change, and social inequity. Singapore is a compelling case study because of its remarkable success in transforming itself into a developed nation through a highly structured, rational, and long-term-oriented planning system. Its approach reflects a strongly technocratic and centralized model, with the government exercising dominant authority in shaping development trajectories through data-driven and scientifically informed concept and master plans. To understand this phenomenon, this study employs the Synoptic, Incremental, Transactive, Advocacy, and Radical Planning (SITAR) framework as the analytical foundation. Based on an extensive literature review and the author’s argumentative analysis, Singapore’s planning practice is most accurately classified under the Synoptic or Rational Comprehensive Planning Model, which prioritizes rationality, consistency, and efficiency. While this model has contributed significantly to policy coherence and effective development outcomes, it also has limitations, particularly regarding public participation and flexibility in responding to evolving social dynamics. Overall, rational planning in Singapore has proven effective in a stable political environment, but it must be complemented by more communicative and inclusive approaches to meet future development challenges.